Spinal Manipulation as a Treatment for Neck Pain: A Systematic Review of Randomized Controlled Trials - Marcelo Guevara Hernández, David; Mireya Ortiz Pérez, Shirley; Alexandra Álvarez Carrión, Sonia; Belén Pérez García, María (ESPOCH Congresses: The Ecuadorian Journal of S.T.E.A.M., 2024)
Background: Cervical pain is one of the most common pathologies in physiotherapy consultations. Currently, there are countless techniques, protocols, and treatments ranging from conservative to invasive. The intervention includes orthopedic manual therapy techniques in patients who present the pathology. To date, several studies apply spinal manipulation as a treatment option for patients with neck pain; however, its effects on pain and disability are unknown. Methodology: A compilation, selection, and analysis of randomized clinical trials was carried out, and studies showed the effect of this technique on the type and origin of pain in patients with neck pain. Data extraction was formulated in tables, and the methodological quality was determined through the physiotherapy evidence database scale. Results: Thirty studies were included that were classified based on the type and origin of pain. In order to determine the effectiveness, it was applied as the only treatment technique or as part of a multimodal treatment. Conclusions: Spinal manipulation has a greater effect on pain and disability when considered as the only treatment technique in patients with acute pain. However, when applied as part of the multimodal protocol, it proves to be effective in chronic, radicular, mechanical, and nonspecific pain. The high heterogeneity of the studies is a limitation of our findings. Keywords: spinal manipulation, neck pain, cervical vertebral, acute pain, chronic pain. Resumen Antecedentes: El dolor cervical es una de las patologías más comunes presente en la consulta de fisioterapia, en la actualidad existen un sin número de técnicas, protocolos y tratamientos que van desde lo conservador hasta lo invasivo, en la intervención se incluye técnicas de terapia manual ortopédica en pacientes que presentan la patología antes mencionada. Hasta la fecha, existen varios estudios que aplican manipulación espinal como opción de tratamiento para pacientes con dolor cervical, sin embargo, se desconocen sus efectos sobre dolor y la discapacidad. Metodología: se realizó la recopilación, selección y análisis de ensayos clínicos aleatorizados que en sus estudios se evidenció el efecto de esta técnica sobre el tipo y origen del dolor en pacientes con cervicalgia, la extracción de datos se formuló en tablas; la calidad metodológica fue determinada a través de la escala de Physiotherapy Evidence Database, Resultados: se incluyeron treinta estudios que fueron clasificados en base al tipo y origen del dolor, para determinar la efectivad, se tomó en cuenta si era aplicada como única técnica de tratamiento o siendo parte de un tratamiento multimodal. Conclusiones: la manipulación espinal tiene mayor eficacia sobre el dolor y la discapacidad al ser considerada como única técnica de tratamiento en pacientes con dolor agudo; sin embargo, cuando es aplicada como parte del protocolo multimodal demuestra ser eficaz en el dolor crónico, radicular, mecánico e inespecífico, la alta heterogeneidad de los estudios es una limitante para nuestros hallazgos. Palabras Clave: manipulación espinal, cervicalgia, vértebras cervicales, dolor agudo, dolor crónico.